PERBANDINGAN PENGUKURAN STRUKTUR PERSAINGAN HERFINDAHL-HIRSCHMAN INDEX DAN CONCENTRATION RATIO INDUSTRI PERBANKAN INDONESIA - Shofwan; Khansa, Ken Ayu (Contemporary Studies in Economic, Finance and Banking, 2022)
This study aims to determine, measure and analyze and compare the structure of banking competition in Indonesia.This study used a sample of 9 banks, each consisting of 4 State-Owned Commercial Banks (BUMN) and 5 National Private Commercial Banks (BUSN) with market share gains based on the largest Third Party Funds in Indonesia. The data analysis method used is concentration ratio analysis using Herfidahl-Hirschman Index (HHI) and Concentration Ratio (CR). The results of the analysis show that there is a difference in results between the ratio of HHI and CR, the HHI ratio shows that the Indonesian banking market is in a monopolistic competition market, while based on the CR ratio, Indonesian banks are in a perfectly competitive market, further analysis shows an increasing level of market concentration and the suitability of the Indonesian banking market with characteristics in the monopolistic market.In addition, based on each group of banks, the group of state-owned banks is in the market of loose oligopoly competition / monopolistic competition, in the Group of National Private Commercial Banks is in the structure of effective / monopolistic competition, while in the group of banks that are classified as large (BUKU IV) it is in the structure of loose oligopoly competition or monopolistic competition.